Disease extent and anti‐tubercular treatment response correlates with Mycobacterium tuberculosis‐specific CD4 T‐cell phenotype regardless of HIV‐1 status. Issue 9 (28th September 2020) - Riou, Catherine; Du Bruyn, Elsa; Ruzive, Sheena; Goliath, Rene T; Lindestam Arlehamn, Cecilia S; Sette, Alessandro; Sher, Alan; Barber, Daniel L; Wilkinson, Robert J
Abstract: Objectives: The development of non‐sputum‐based assays for tuberculosis (TB) diagnosis and treatment monitoring is a key priority. Recent data indicate that whole blood‐based assays to assess the phenotype of Mycobacterium tuberculosis (Mtb)‐specific CD4 T cells hold promise for this purpose and require further investigation in well‐characterised TB cohorts. In this study, we investigated the relationship between the phenotypic signature of Mtb‐specific CD4 responses, TB disease extent and treatment response. Methods: Using flow cytometry, we measured the expression of phenotypic and functional markers (HLA‐DR, CD27, CD153, KLRG1, IL‐2, MIP‐1β, TNF‐α and IFN‐γ) on Mtb‐specific CD4 T‐cells in whole blood from 161 participants of varying TB and HIV status. TB disease extent was graded as a continuum using the Xpertct value, C‐reactive protein, Timika radiographic score and monocyte/lymphocyte ratio. Results: The phenotypic profile of Mtb‐specific CD4 T cells pre‐anti‐tubercular treatment (ATT) strongly correlated with disease extent, irrespective of HIV status. ATT associated with major changes in the phenotype of Mtb‐specific CD4 T cells, with decreased expression of HLA‐DR and increased CD27 and CD153 expression. Principal component analysis showed an almost complete separation between latent TB infection (LTBI) and active TB (aTB) pre‐ATT groups, whereas the profile of the aTB post‐ATT group overlapped with the LTBI group. However, in patients experiencing treatment failure or relapse, no significant changes were observed in Mtb‐specific CD4 T‐cell phenotype pre‐ and post‐ATT. Conclusion: Whole blood‐based assays of Mtb‐specific CD4 T‐cell activation and maturation markers can be used as non‐sputum‐based biomarkers of disease extent and treatment monitoring in TB, regardless of HIV‐1 status. Abstract : A better understanding of the relationship between host immune responses, tuberculosis (TB) disease severity and treatment outcome is key to the development of novel TB diagnostic and treatment monitoring tools. In this study, we defined the profile of Mycobacterium tuberculosis ‐specific IFNγ + CD4 T‐cell response in TB patients, analysed its evolution after completion of a standard anti‐tubercular treatment regimen and evaluated how the host CD4 response associates with clinical TB extent and treatment response.